Preliminary evaluation of the ethnoclimatic and ethnogeomorphologic knowledge of fishermen of the coast of the Municipality of Goiana - state of Pernambuco / Brazil - Fernandes-da-Silva, Roberta Kelly; Martins-Lopes, Vanessa; Girão, Osvaldo (Revista Geográfica de América Central., 2018)
This study aimed at preliminarily finding the ethnoclimatic and ethno-geomorphological knowledge of three fishing communities located on the municipality of Goiana, in the state of Pernambuco. This aimed at identifying how fishermen understand the knowledge about the climatic seasonality and the forms and functions of the coastal reliefs, as well as classifying the physical / natural environment in which they live. Bibliographical surveys were carried out and visits to the surveyed communities were made to recognize the physical/natural environment where qualitative interviews were subsequently conducted. Understanding the importance of ethno-knowledge and the experiences that the residents of the communities have in relation to the dynamics existing in the environment in which they practice fishing, may contribute effectively to actions developed by the public power from the participation of residents with their knowledge, experience and practices.